Meningkatkan Kemampuan Siswa untuk Membaca Awal melalui Strategi Bimbingan Langsung kepada Siswa Kelas I SDN Dinoyo 2 Malang - Muh. Zuhdy Hamzah (Nuances of Indonesian Language, 2021)
The problem in this research is whether the direct guidance strategy learning model can improve the beginning reading ability of grade 1 students at SDN Dinoyo 2 Malang. This study aims to improve the ability to begin reading by using direct guidance strategies. This research is a classroom action research (PTK). The research subjects were students in grade 1 with a total of 22 students. The research location is SDN Dinoyo 2 Malang. Data collection techniques by observation, and tests. Data analysis was performed by qualitative descriptive analysis. The results of teacher and student observations in this study on average were in the good category. This research shows, (1) learning planning with direct guidance strategies is carried out with preparation in the form of learning implementation plans, methods, strategies and media in the form of reading source designs through text sheets. (2) The implementation of direct guidance strategies has improved students' reading learning, so that the learning atmosphere becomes more pleasant, (3) The learning outcomes with direct guidance strategies have been able to improve the ability to read at the beginning. This is evidenced by the test results in cycle one with a class average score of 68.2% or in the sufficient category. In cycle two students have experienced an increase in the class average score of 90.9% or are in the very good category.